The structure of transparency oversight bodies and administrative contexts - Ros-Medina , José Luis; Mayor Balsas , José Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
There are few studies on the configuration of transparency oversight bodies and administrative contexts from a holistic perspective. This is even more the case for those that study in depth the different dimensions studied in the literature from a qualitative point of view. This paper therefore aims to take a small step forward by providing some empirical evidence in this regard. A comparative analysis is conducted on the basis of a series of in-depth interviews carried out in the Canary Islands and Navarre with representatives of both the control bodies and the corresponding Administration. This analysis is based on the levels of transparency and management of the right of access, the training and administrative culture of public employees, the demand for transparency, the configuration of executive governments and their ideology, and its institutional openness
Keywords: Transparency; oversight bodies; public employees; ideology; institutional openness